2008
DOI: 10.2106/jbjs.g.01246
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Management Improves the Rate of Early Osteoporosis Treatment After Hip Fracture

Abstract: An active role by orthopaedic surgeons in the management of osteoporosis improves the rate of treatment at six months following a hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 31 publications
2
58
0
Order By: Relevance
“…Patient involvement was not reported by any of the studies. In four studies, the authors reported specific barriers to change that the intervention was tailored to address [37, 40, 42, 44]. Only one study reported that they had carried out substantial exploratory work to identify them [40] (literature reviews and qualitative in-depth interviews with healthcare professionals).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient involvement was not reported by any of the studies. In four studies, the authors reported specific barriers to change that the intervention was tailored to address [37, 40, 42, 44]. Only one study reported that they had carried out substantial exploratory work to identify them [40] (literature reviews and qualitative in-depth interviews with healthcare professionals).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported that they had carried out substantial exploratory work to identify them [40] (literature reviews and qualitative in-depth interviews with healthcare professionals). In two of the four studies, barriers were not identified and discussed until the end of the paper [37, 44]. Only one study designed the intervention to address all of the identified barriers [40]; the others offered no explanation as to why they had chosen particular barriers to target over others, with one study selecting a single barrier from a long list of barriers [44].…”
Section: Resultsmentioning
confidence: 99%
“…Comparative studies conducted on orthopedic surgeon and physician-based interventions for improving osteoporosis management after hip fracture show awareness of orthopedic surgeon has a greater effect on osteoporosis management rates after hip fracture (20, 23). In particular, Miki et al (22) reported the effects of osteoporosis management initiated by an orthopedic team and by primary care physicians (22). The osteoporosis treatment rate 6 months after hip fracture was higher for the orthopedic team (58%) than for the primary care physicians (29%) (22).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Miki et al (22) reported the effects of osteoporosis management initiated by an orthopedic team and by primary care physicians (22). The osteoporosis treatment rate 6 months after hip fracture was higher for the orthopedic team (58%) than for the primary care physicians (29%) (22). Our study also showed an improved medication rate of osteoporosis from 15% to 32%.…”
Section: Discussionmentioning
confidence: 99%
“…adherence to treatment [4][5][6][7][8][9][10][11][12][13][14][15]. Previous research suggests that the lack of awareness of current guidelines is one of the main obstacles to initiating therapy and that multifaceted interventions are required to improve treatment results as single interventions or basic information dissemination showed no significant increase in treatment rates [4,11,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%